1977
DOI: 10.1172/jci108888
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanum Probe Studies of Cellular Pathophysiology Induced by Hypoxia in Isolated Cardiac Muscle

Abstract: A B S T R A C T This study was undertaken to evaluate directly the relationship between evolution of irreversible myocardial injury induced by hypoxia in an isolated papillary muscle preparation and the development of pathophysiological alterations related to severely impaired membrane function. An ionic lanthanum probe technique was employed as a cytochemical marker to monitor the progression of cellular injury, and data from this cytologic technique were correlated with ultrastructure and measurements of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

1980
1980
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Using iodoacetate as a metabolic inhibitor, it has been demonstrated that myocardial cells can withstand large decreases in cellular ATP levels without developing sarcolemmal membrane defects. Since the development of these sarcolemmal defects is a hallmark ofirreversible injury (25,26), these results provide additional evidence that the release of arachidonic acid is linked to the onset of irreversible injury of cultured myocardial cells during ATP depletion. However, there are several reasons for interpreting the results of the present study with caution.…”
Section: Discussionmentioning
confidence: 71%
“…Using iodoacetate as a metabolic inhibitor, it has been demonstrated that myocardial cells can withstand large decreases in cellular ATP levels without developing sarcolemmal membrane defects. Since the development of these sarcolemmal defects is a hallmark ofirreversible injury (25,26), these results provide additional evidence that the release of arachidonic acid is linked to the onset of irreversible injury of cultured myocardial cells during ATP depletion. However, there are several reasons for interpreting the results of the present study with caution.…”
Section: Discussionmentioning
confidence: 71%
“…In intact ischemic heart models, previous studies have demonstrated the presence of sarcolemmal membrane defects by electron microscopy, which correlated with the time course of the onset of irreversible injury and the accumulation of tissue calcium (1,2). Previous studies in a perfused rabbit septal model related the decreases in myocardial contractile performance during ischemia with the development of increased sarcolemmal membrane cation permeability (3). Acute myoAddress reprint requests to Dr. Chien. Received for publication 8 May 1984 and in revised form 11 January 1985. cardial infarction in man is characterized by leakage of cytosolic enzymes across the sarcolemmal membrane into the vascular space (4).…”
Section: Introductionmentioning
confidence: 99%
“…THERE is increasing evidence which indicates that surface structure of the myocardial cell is damaged by ischemia and anoxia (Jennings et al, 1975;Hearse et al, 1975;Frank et al, 1980) and that this damage leads to marked changes in cellular permeability to calcium (Ca) (Burton et al, 1977;Shen and Jennings, 1972). In addition, it is well known that exposure of the myocardium to solutions that contain no Ca produces major changes in membrane permeability upon reintroduction of Ca-the "Ca paradox" (Zimmerman and Hulsmann, 1966;Crevey et aL, 1978).…”
mentioning
confidence: 99%